Cardiac screening prior to return to play after SARS-CoV-2 infection: focus on the child and adolescent athlete: A Clinical Consensus Statement of the Task Force for Childhood Health of the European Association of Preventive Cardiology - D'Ascenzi, Flavio; Castelletti, Silvia; Adami, Paolo Emilio; Cavarretta, Elena; Sanz-De La Garza, Maria; Maestrini, Viviana; Biffi, Alessandro; Kantor, Paul; Pieles, Guido; Verhagen, Evert; Tiberi, Monica; Hanssen, Henner; et al. (European Journal of Preventive Cardiology, 2022)
Cardiac sequelae after COVID-19 have been described in athletes, prompting the need to establish a return-to-play (RTP) protocol to guarantee a safe return to sports practice. Sports participation is strongly associated with multiple short- and long-term health benefits in children and adolescents and plays a crucial role in counteracting the psychological and physical effects of the current pandemic. Therefore, RTP protocols should be balanced to promote safe sports practice, particularly after an asymptomatic SARS-CoV-2 infection that represents the common manifestation in children. The present consensus document aims to summarize the current evidence on the cardiac sequelae of COVID-19 in children and young athletes, providing key messages for conducting the RTP protocol in paediatric athletes to promote a safe sports practice during the COVID-19 era.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adolescent; Athlete's heart; Children; COVID-19; Return to play; Screening; Sports cardiology